Late-Holocene diatom community response to climate driven chemical changes in a small, subarctic lake, Northwest Territories, Canada. (July 2021) - Hamilton, Paul B; Hutchinson, Scott J; Patterson, R Timothy; Galloway, Jennifer M; Nasser, Nawaf A; Spence, Christopher; Palmer, Mike J; Falck, Hendrik
The paleolimnological record of diatoms and climate, spanning the last 2800 years, was investigated in a small subarctic lake (Pocket Lake) that from AD 1948 to 2004 was contaminated by gold smelting waste. An age-depth model was constructed using a combination of 210 Pb, 14 C, and tephra to determine a 2800 year history of lake ontogeny (natural aging), biological diversity, and regional climate variability. Diatoms form six strong paleoecological assemblages over time in response to changes in local hydrological and sedimentological conditions (including metals). Selected environmental variables explained 28.8% of the variance in the diatom assemblages, with Fe, Ca, and sediment end member distribution being important indicators. The diatom assemblages correlated to the Iron Age Cold Epoch (2800–2300 cal BP), Roman Warm Period (2250–1610 cal BP), Dark Age Cold Period (1500–1050 cal BP), Medieval Climate Anomaly (ca. 1100–800 cal BP), and the Little Ice Age (800–200 cal BP). The disappearance of Staurosira venter highlights the change from the Iron Age Cold Epoch to the Roman Warm Period. After deposition of the White River Ash (833–850 CE; 1117–1100 cal BP), transition to circumneutral conditions was followed in tandem by a transition to planktic influenced communities. Ten discrete peaks of Cu, Pb, and Zn were observed and attributed to soluble mobility from catchment soils through enhanced seepage and spring snowmelt. The prominent metal spikes were aligned with increases in Brachysira neoexilis . Downward mobilization of arsenic and antimony from contaminated surficial sediments highlight the problem of post depositional industrial contamination of paleosediments. Results demonstrate that paleoclimatic changes in the region, modulated by solar radiation, impacted temperature and precipitation in the lake catchment, influencing temporal shifts in diatom ecology. Changes in diatom taxa richness provided valuable information on the relative influence of water quality (planktic taxa) and sediment input (benthic taxa). The diatom assemblage succession also provides evidence that natural aging over time has played a role in the ecological evolution of the lake.